Importance of growth method and substrate-induced crystalline quality in Al/Gd0.2Ca0.8MnO3/Au memristor devices - Angervo, I; Antola, A; Vaimala, T; Malmi, A; Schulman, A; Huhtinen, H; Paturi, P (IOP Publishing, 2025)
We report on the impact of the growth method and substrate-induced crystalline quality on the performance of planar Al/Gd0.2Ca0.8MnO3/Au memristor devices. Structural, magnetic, and resistive properties were thoroughly examined for fundamental characterizations, with a particular emphasis on their correlation with the memristive properties of fabricated devices. Our findings suggest that memristor structures grown on single crystal SrTiO3 substrates using pulsed laser deposition (PLD) consistently exhibit superior crystalline quality compared to those fabricated using chemical solution deposition and on silicon-based substrates. Despite variations in growth method and substrate, all memristor structures display typical resistive switching (RS) behaviour, distinguishing between high-resistance and low-resistance states. However, endurance and retention measurements demonstrate that memristor structures produced via PLD on single crystalline SrTiO3 demonstrate the most favourable RS properties. To elucidate the mechanisms underlying the differences in RS behavior across substrates and deposition methods, we extensively discuss these issues in the context of structural distortion and conduction mechanisms.